How to increase community-wide resilience and decrease inequalities due to adverse childhood experiences (ACEs): Strategies from Walla Walla, Washington. Issue 1 (2nd January 2021) - Longhi, Dario; Brown, Marsha; Barila, Theresa; Reed, Suzette Fromm; Porter, Laura
Abstract: Adverse childhood experiences (ACEs) negatively impact community-level social problems, education, work, mental, and physical health beyond the effects of economic and political inequality. This paper summarizes the evidence that community-wide resilience moderates such impacts and examines how resilience can be increased by strategic interventions focused on community capacity building; Trauma-Informed Practices (TIPs) by staff in community organizations; and cultural change. Findings from three formative research evaluations in Walla Walla, Washington, show how community capacity was increased, trauma-informed practices were implemented across local organizations, and a school's culture was transformed. Common elements of change were shifts in: mindsets, collaborative relationships, and organizational values/structures. These changes enabled the adoption of scaffolded, equity-based, innovative interventions that can potentially decrease economic and racial/ethnic disparities by preventing the progression of ACEs into adult adversities, poverty, and discrimination.